Pengaruh Faktor Minat, Motivasi Dan Lingkungan Masyarakat Terhadap Kesulitan Belajar Pada Mata Pelajaran Ekonomi Siswa Kelas X Di SMA Negeri 5 Padang - Dessyta Gumanti; Reni Respita; Wilgasia (Kilau Publishing, 2025)
This study aims to analyze the influence of interest, motivation, and the social environment on students’ learning difficulties in Economics among Grade 10 students at SMAN 5 Padang, both partially and simultaneously. The study employed a descriptive quantitative approach. The population consisted of 412 Grade 10 students, with a sample of 80 students selected through proportional random sampling. Data were collected using a questionnaire and analyzed using multiple linear regression with SPSS version 26. Hypotheses were tested using the t-test for partial effects and the F-test for simultaneous effects. The results show that interest does not have a significant effect on learning difficulties (coefficient 0.377; t-value 0.995 < t-table 1.992), while motivation has a significant effect (coefficient 0.427) and the social environment also has a significant effect (coefficient 0.509) on learning difficulties. Simultaneously, interest, motivation, and the social environment influence students’ learning difficulties. These findings indicate that learning motivation and a supportive social environment play an important role in reducing learning difficulties, whereas interest does not show a significant partial effect.